The scientific justification of the assessment system and professional risk management in industrial enterprises - Lezhnina, M.; Sharavara, L. P.; Шаравара, Лариса Павлівна (My University, 2020)
In the context of the new ideology of preventative medicine, occupational safety should be seen as predicting and assessing risks and managing them. In recent years, under the guidance of international organizations, risk assessment has become widespread in countries around the world. The Professional risk data must be an organic component of the system of hygienic regulation for harmful production factors and be used as basic criteria to substantiate the maximum permissible risks and maximum permissible concentrations of harmful factors. Today the concept of risk is considered as the main mechanism of development and making decisions both internationally, nationally or regionally, as well as at the level of individual production almost worldwide and by almost every international organization.
Keywords: professional risk; professional risk management system